Lessons From Lockdown: The Educational Legacy of COVID-19 London and New York by Tony Breslin - Majoros, Noemi (Central European Journal of Educational Research, 2021)
Bibliography of the reviewed book: Tony, B. (2021). Lessons from lockdown: The educational legacy of COVID-19. Routledge.